Adaptive Bandwidth Allocation in Broadband Networks - Lauks, G. (Elektronika ir Elektrotechnika, 2006)
MPLS and DiffServ have been widely accepted as the service model to adopt for providing Quality of Services (QoS) over next generation IP networks. The combination of MPLS and DiffServ presents a very attractive strategy to broadband network providers. Bandwidth Allocation mechanism in DiffServ guaranties to meet the QoS requirements for all types of services. The objectives of this paper are to simulate and estimate the efficiency of Maximum Allocation with Reservation (MAR) method in small network cases. Problem statement of MAR is enhanced with bandwidth utilization variables. Simulation results illustrate the efficiency of traffic predictors and MAR in small network cases. Ill. 3, bibl. 8 (in English; summaries in English, Russian and Lithuanian).